Criticality mitigation in a quasi-constant coupling position independent resonant IPT network. Issue 8 (8th June 2018) - Pacini, Alex; Mastri, Franco; Masotti, Diego; Costanzo, Alessandra
Abstract: This paper discusses some significant design issues that are faced in resonant inductive system for wireless power transfer 'on the move'. The targeted system adopts a single AC source to power a sequence of transmitting ( Tx ) coils, placed along the Rx path, whose geometry is optimized to minimize the variations of coupling for every possible Rx position. To retain a constant coupling coefficient, two nearby Tx coils are series-connected and simultaneously activated, establishing a path without any theoretical bound on its length, by a suitable switching network. This work analyzes the effects of asynchronous switching times, which are rigorously accounted for and minimized by a proper design of the compensating circuit elements, minimizing both the voltage spikes and the over currents on the coils, while keeping the system at resonance. A prototype operating at 6.78 MHz is built and experimental validations are carried out to verify the feasibility of a constant coupling link without experiencing the mentioned effects, but the adopted procedure is general and independent on its size or frequency.